2022
DOI: 10.3390/molecules27186116
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sulfur Compounds in Vegetable and Mushroom Aroma

Abstract: At the base of the food pyramid is vegetables, which should be consumed most often of all food products, especially in raw and unprocessed form. Vegetables and mushrooms are rich sources of bioactive compounds that can fulfill various functions in plants, starting from protection against herbivores and being natural insecticides to pro-health functions in human nutrition. Many of these compounds contain sulfur in their structure. From the point of view of food producers, it is extremely important to know that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 143 publications
(189 reference statements)
2
8
0
Order By: Relevance
“…Our results demonstrate that DMDS is one of the compounds involved in mediating the preference of Dbus for oviposition on mushrooms. This observation is consistent with prior studies reporting the emission of sulfur compounds, including DMDS, from mushrooms 55,56 .…”
Section: Discussionsupporting
confidence: 93%
“…Our results demonstrate that DMDS is one of the compounds involved in mediating the preference of Dbus for oviposition on mushrooms. This observation is consistent with prior studies reporting the emission of sulfur compounds, including DMDS, from mushrooms 55,56 .…”
Section: Discussionsupporting
confidence: 93%
“…Sulfur-containing compounds (aldehydes, sulfides, thiols, and thiophenes) are important contributors to meat flavor and aroma [ 9 , 10 ]. However, sulfur-containing compounds are also primary contributors of vegetable and mushroom flavors and aromas [ 20 ]. This abundance of sulfur compounds is due to the various precursors (sulfur-containing amino acids, thiamine, and glucosinolates) found in both animal and plant food products.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the addition of thiamin to PBMA may also explain the increase in sulfur-containing compounds. Diallyl sulfide is responsible for garlic aromas and is derived from Brassica and Allium vegetables [ 20 ]. However, it can appear in animal products as well.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal decomposition of sulfurous species during processing has been shown and discussed in this context earlier. , An investigation into gaseous cooking emissions demonstrated that thermal processing releases dimethyl sulfide from vegetables . Up to date, the flavor of PBMA lags behind the flavor of meat. , Even though plants are known to produce many sulfurous aroma compounds and cysteine, as well as thiamine, which are present in plants, , our finding contributes to explaining the still-existing differences between meat and PBMA flavor. To better mimic the original taste of meat, sulfurous reaction precursors are spiked into PBMA raw material to compensate for this deficiency. , Analysis of PBMA vapor might help to find better formulations or additives to achieve better consumer acceptance by creating a head space profile closer to meat.…”
Section: Results and Discussionmentioning
confidence: 54%
“…53 Up to date, the flavor of PBMA lags behind the flavor of meat. 45,52 Even though plants are known to produce many sulfurous aroma compounds and cysteine, as well as thiamine, which are present in plants, 46,54 our finding contributes to explaining the still-existing differences between meat and PBMA flavor. To better mimic the original taste of meat, sulfurous reaction precursors are spiked into PBMA raw material to compensate for this deficiency.…”
Section: Journal Of Agricultural Andmentioning
confidence: 77%